2016
DOI: 10.1080/10420150.2016.1194413
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of structural damage in amorphous silica induced by swift heavy-ion radiation

Abstract: In this paper, the radiation defects induced by the swift heavy ions and the recoil atoms in amorphous SiO 2 were studied. The energy of recoil atoms induced by the incident Au ions in SiO 2 was calculated by using Monte Carlo method. Results show that the average energies of recoils reach the maximum (200 eV for Si and 130 eV for O, respectively) when the incident energy of Au ion is 100 MeV. Using Tersoff/zbl potential with the newly built parameters, the defects formation processes in SiO 2 induced by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this study, 120 keV He can initiate maximum 52.5 keV Si, 76.8 keV O and 90 keV C primary knock-on atoms (PKA). These PKA energy are much larger than the threshold displacement energy for Si, O, C elements (20–40 eV) 31 , 32 , giving rise to ballistic displacements of atoms within materials. It is generally known that nuclear stopping processes can lead to net bond breaking in irradiated materials.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, 120 keV He can initiate maximum 52.5 keV Si, 76.8 keV O and 90 keV C primary knock-on atoms (PKA). These PKA energy are much larger than the threshold displacement energy for Si, O, C elements (20–40 eV) 31 , 32 , giving rise to ballistic displacements of atoms within materials. It is generally known that nuclear stopping processes can lead to net bond breaking in irradiated materials.…”
Section: Discussionmentioning
confidence: 93%
“…Time-resolved MD simulations of the Si–O–C network matrix, (a) amorphous SiOC model, and (b) model in the peak-damage state, and only the atoms with energies above displacement threshold energy are shown, which is 33.5 eV for Si, 16.3 eV for O, and 24.3 eV for C. , (c) Top view of the cascade with maximum cascade size. Close-ups of the model showing microstructural changes in the (d) initial state, (e) peak-damage state, and (f) final state.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of radial cracks and axial cracks appeared along the periphery of the fused silica [12][13][14] that was accompanied by material injection. Zhen et al [15] and Umari et al [16] analyzed the structures before and after the breakdown of fused glass on the microscale. These studies have shown that ionization breakdown and plasma are the main causes of glass damage, and the resulting plasma shock waves cause a more extensive damage.…”
Section: Introductionmentioning
confidence: 99%